Restoration of angiogenic capacity in senescent endothelial cells by a pharmacological reprogramming approach. - Katrin Kalies; Kai Knöpp; Susanne Koch; Claudia Pilowski; Leonie Wurmbrand; Daniel Sedding (PLoS ONE)
Senescent endothelial cells (EC) are key players in the pathophysiology of cardiovascular diseases and are characterized by a reduced angiogenic and regenerative potential. Therefore, targeting these cells has been suggested as an effective therapeutic strategy to reduce vascular disease burden and potentially improve health and lifespan of humans. Here, we aimed to establish a pharmacological, partial reprogramming strategy to improve replicative senescent endothelial cell function in the context of angiogenesis. We demonstrate that our treatment improves tube formation and sprouting capacity but also increases proliferation and migration capacity in vitro. Further, inflammation and DNA damage were reduced in the replicative senescent cells. These processes were initiated by a short and timely-restricted overexpression of the Yamanaka-factors induced by our pharmacological strategy. The advantage of these compounds is that they are FDA approved in their respective concentrations which could pave the way for use in a clinical setting.